2004
DOI: 10.1111/j.1467-8535.2005.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

When group work leaves the classroom does group skills development also go out the window?

Abstract: In moving towards what Lemke (1996) terms the 'interactive learning paradigm', higher education has adopted two key principles consistent with group learning technologies:• learning is always mediated by and occurs through language (Falk, 1997;Gee, 1997); and • learning is distributed across a range of other people, sites, objects, technologies and time (Gee, 1997).A third and relatively recent principle to emerge on the higher education scene that seems to 'contradict' accepted views of group learning technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…As a result, the participants were unable to create a community of learning as they failed to connect socially with other learners by appreciating other learners' efforts and respecting the privacy of others. The findings concur with other studies on the importance of effective online communication skills (Johnson & Stanne, 2000;Baskin, Barker, & Woods, 2005;Jahng, Nielsen, & Chan, 2010). The findings supported the findings of the study carried by Hooper and Kalidas (2012) that indicated that the Netiquette depended on the multiple audiences of the Facebook users.…”
Section: Discussionsupporting
confidence: 82%
“…As a result, the participants were unable to create a community of learning as they failed to connect socially with other learners by appreciating other learners' efforts and respecting the privacy of others. The findings concur with other studies on the importance of effective online communication skills (Johnson & Stanne, 2000;Baskin, Barker, & Woods, 2005;Jahng, Nielsen, & Chan, 2010). The findings supported the findings of the study carried by Hooper and Kalidas (2012) that indicated that the Netiquette depended on the multiple audiences of the Facebook users.…”
Section: Discussionsupporting
confidence: 82%
“…Comparable results were found in a study on the role of ICT in promoting group skills development in graduate students (Baskin, Barker & Woods, 2005). The researchers concluded that ‘while these [technologies] helped to centralise decision‐making processes and exchange of ideas for students, none of these... seemed to directly support convergent group work processes across the sample’ (Baskin et al , 2005, p. 19).…”
Section: Findings and Discussionmentioning
confidence: 47%
“…The importance of clarity in project design so that students know what is expected of them is reinforced by other researchers (Baskin, Barker and Woods, 2005;Baldwin and Keating, 1998). From the perspective of action learning, however, there are also lessons to be learnt about cultivating independent attitudes to learning.…”
Section: Discussionmentioning
confidence: 92%